Southern Oil Company (Mobile, Ala.) journal and letterbooks - Southern Oil Company (Mobile, Ala.)
Journal and letterbooks kept by N. Bradner Smith, resident agent and superintendent of the Southern Oil Company, Mobile, Ala.
Firm engaged in the resin and pitch trade, Mobile, Ala.
Collection material in English.
Keywords: Smith, N. Bradner; Gums and resins industry -- Alabama -- Mobile; Pitch; Mobile (Ala.) -- Commerce